USE OF COMPUTER TECHNOLOGIES IN DIAGNOSTICS, TREATMENT, AND REHABILITATION IN PEDIATRIC TRAUMATOLOGY - Kayumov Ikromjon Qahramonovich; Jalilov Asliddin Zavhiddinovich (Bright Mind Publishing, 2025)
This article discusses the role and capabilities of computer technologies in the field of pediatric traumatology. Today, the possibility of carrying out the stages of diagnosis, treatment, and rehabilitation more accurately and conveniently based on digital technologies is expanding. Furthermore, Artificial Intelligence (AI) and 3D technologies are increasingly being used in medical practice, contributing to an increase in the effectiveness of the treatment process in pediatric traumatology.
Keywords: pediatric traumatology, computer technologies, diagnostics, treatment, rehabilitation, artificial intelligence, 3D technologies.